Geschichte der arabischen Litteratur - Brockelmann, Carl, 1868-1956. (Leiden Leiden Leiden Leiden)
5 cilt ( 1. c. ix, 676 sayfa ; 2. c. xiv, 686, [1] sayfa ; Ek 1. c. xvii, 973 sayfa ; Ek 2. c. 960 sayfa ; Ek 3. c. x, 1326 sayfa